THE CONTRIBUTION OF LABOR FORCE, MATERIAL CAPITAL, HUMAN CAPITAL AND TOTAL FACTOR PRODUCTIVITY TO ECONOMIC GROWTH BASED ON THE CHANGE OF EMOTIONAL BEHAVIOR - Zhang, Wenai; Liu, Li (The international journal of neuropsychopharmacology, 2022)
Abstract Background Promoting the sustained and stable growth of the national economy is the eternal goal of economic theory researchers and policy makers. So, what is the fundamental source of promoting a country's sustainable economic growth? Research Objects and Methods From the perspective of labor, physical capital, human capital and total factor productivity, this paper makes an empirical study on the contribution of various input factors to economic growth in 36 OECD countries from 1990 to 2017. In order to analyze the impact of this strategy on the change of livelihood capital on emotion, and provide effective measures and basis for alleviating psychological pressure. In this study, 500 subjects in Southwest China were investigated with Depression Anxiety Stress Scale (DASS-21). Results The results show that: (1) the output elasticity of labor, physical capital and human capital input factors is statistically significant, indicating that input has an important impact on economic growth. (2) The total contribution share of investment accounts for about 1 / 3, of which labor force accounts for about 24%, and the proportion of physical capital and human capital accounts for 5% and 6% respectively is similar and relatively small. (3) Total factor productivity (TFP) is the most important driving force of economic growth, accounting for 2 / 3 of economic growth. (4) The contribution of labor and material capital showed a slow upward trend, the contribution of human capital was basically stable, and the contribution of total factor productivity showed a slow downward trend. (5) Exploring the sources of economic growth has important policy implications not only for OECD countries but also for developing countries. Taking the emotional grouping as the independent variable, the group conducted a one-way multivariate analysis of variance on the fluency and novelty of aut, box's M = 24.05, P < 0.001. The result shows that the data is not suitable for multivariate analysis of variance, so the emotional grouping is used as the independent variable to analyze the fluency and novelty of aut by one-way ANOVA respectively. Specifically, the main effect of emotion on aut fluency is significant, f (2, 99) = 6.43, P = 0.002, η 2 p= 0.12. Post hoc comparison showed that the anger group (M = 11.26, SD = 6.20) was higher than the neutral emotion group (M = 7.26, SD = 3.44, P = 0.002, Cohen's d = 0.80), with no other significant difference (see Figure 2D). The main effect of emotion on the novelty of aut was significant, f (2, 99) = 7.84, P < 0.001, η 2 p = 0.14. Post hoc comparison showed that the anger group (M = 15.29, SD = 8.85) was higher than the sadness group (M = 11.21, SD = 5.50, P = 0.042, Cohen's d = 0.55) and the neutral emotion group (M = 8.91, SD = 5.23, P = 0.001, Cohen's d = 0.88). Conclusion All sectors of society should fully understand the importance of emotional factors of relevant groups in rehabilitation, actively improve the surrounding environment and the respective roles of both sides, pay special attention to their own virtual technology language and behavior, and shift from single display to multi-dimensional management, coordinator and collaborator. In the process of output, actively present personalized psychology to patients, flexibly organize activities, strive to create a relaxed and harmonious rehabilitation atmosphere, create a friendly and mutual aid business environment, encourage and guide patients to adjust their psychology to the best state. Acknowledgements The work is supported by Open Fund Project of Research Center for Economy of Upper Reaches of the Yangtse River of Chongqing Technology and Business University (KFJJ2018002). The author is highly grateful to the editor and anonymous referees for their valuable comments and constructive suggestions which help to improve the present form of this paper.